The Impact of COVID-19 on Stock Market Performance: Evidence from the Dhaka Stock Exchange Indices - E Jannat, Nur; Ahmed, Md Tuhin; Sadekin, Md Nazmus; Alam, Md Mahbub; Muzib, Md Moniruzzaman (South Asian Journal of Social Sciences and Humanities, 2025)
The COVID-19 pandemic sent shockwaves through capital markets worldwide, and the Dhaka  Stock Exchange (DSE) was no exception. This research paper examines the impact of COVID 19 on three of the key indices in the DSE, such as the Broad Index (DSEX), the Sharia Index  (DSES), and the blue-chip index (DS30). Exploiting daily price data from January 2015 to  December 2021, respectively, and fitting the GJR-GARCH (1,1) model, the paper investigates  the effects of the pandemic on market volatility and returns in the special circumstances of the  capital market of Bangladesh. Results indicate that (i) the COVID-19 outbreak witnessed a  great surge in volatility in all three indices, (ii) DSEX had to witness the highest volatility, and  DS30 had the lowest potent impact of volatility, and (iii) there was a positive association  between COVID-19 and market returns within the sample period. The heightened volatility  may be attributed to pre-existing struggles in the DSE, the initial panic caused by the outbreak,  and the subsequent policy responses. Conversely, immediate policy interventions—such as the  introduction of floor prices and circuit breakers—appear to have contributed to positive returns.  In order to lessen the effects of financial shocks, the study emphasizes the significance of  spreading good news and putting in place prompt market-stabilizing measures.
Keywords: COVID-19; DSEX; DSES; DS30; Volatility